The role and prospect of nanomaterials in polymeric membrane for water and wastewater treatment: a state-of-the-art overview - Ismail, Ahmad Fauzi (Trans Tech Publications, 2014)
The efforts and attempts made in the past decades have witnessed a considerable amount of research interest in potential of various inorganic nanomaterials for the development and innovative environmental applications. Inorganic nanofillers such as metal oxides nanoparticles, carbon nanotubes and silver nanoparticles are incorporated into polymeric membranes to render the desired properties, i.e high flux, high rejection and enhanced fouling resistance to suitably applied in liquid-based filtration for waste and wastewater applications. This brief review highlights the state-of-the-art overview in the recent progress and advancement made in the utilization of nanofiller/polymer nanocomposite to remediate the current bottlenecks and issues that stumble the further development of the conventionally used polymeric membranes.